CHANGES IN PLACE OF DEATH PREFERENCES IN PATIENTS RECEIVING SPECIALIST PALLIATIVE CARE: A RETROSPECTIVE CASE NOTE REVIEW. Issue 1 (1st March 2013) - Evans, R; Finucane, A; Vanhegan, L; Arnold, L; Oxenham, D
Abstract : Introduction: To have choice and control over where death occurs is considered central to a good death. In recognition of this, most end of life care strategies promote the need to support people to die in their place of choice. Previous studies suggest that preferences may change over time, however few studies have examined the type of changes in preference that occur in patients receiving specialist palliative care (SPC). Aims and Methods: To explore changes in preferred place of death (PPD) for patients receiving SPC; and to examine the pattern of these changes. A retrospective case note review of all patients who died under the care of Marie Curie Hospice Edinburgh during a 6-month period was undertaken (311 patients). Caldicott Guardian approval was given for this study. Results: 204 patients were asked about PPD more than once; 57% of these changed their mind at least once. Most changed from 'preference unknown' to home (33%) or to hospice (39%). 44% of patients who had an inpatient stay changed their preference compared to 27% who did not have an inpatient stay. Of those choosing the hospice, 88% had been an inpatient compared to 39% of those choosing home. The majority of patients wished to die in the location where they were asked about their preference: Care home: 100%, Hospice: 81% Home:78%. Conclusions: Preference for place of death changes; more patients make a categorical choice over time. Most patients choose a place they are familiar with. Patients who have experienced hospice admission are more likely to choose this option.